Three "Budrysow": Author’s Text - Lineal Translation - Poetic Translation - Feduta, Aleksandr (Respectus Philologicus, 2004)
The article pertains to the context of the first presentation of Adam Mickiewicz’s ballad "Trzech Budrysów (Ballada litewska)" to Russian readers. For the first time its word-for-word (lineal) translation was published by Faddei Bulgarin in 1829. Alexander Pushkin had his poetical translation published in 1834. Bulgarin’s translation might have been an incentive for Pushkin’s translation, although it is clear that Pushkin referred to the original text of Mickiewicz’s ballad. Certain stylistic peculiarities characteristic of the translators can be observed in both translations. Pushkin used the translation of Mickiewicz’s ballad as a form of competition with the Polish poet in the technique of versification. At the same time, since the translation was published after the ideological confrontation between the two poets regarding the repression of the Polish revolt of 1830–1831 (which was supported and praised by Pushkin), the publication of Pushkin’s translation of "Trzech Budrysów (Ballada litewska)" became an attempt of the Russian poet to show that the ideological confrontation does not always result in personal and poetic confrontation. Attached to the article is the lineal translation of the ballad performed by Faddei Bulgarin.